Ultrasonic cavitation assisted deposition of catalytically active metals on nitrogen-doped and non-doped carbon nanotubes — A comparative study - Vanyorek László; Prekob Ádám; Hajdu Viktória; Muránszky Gábor; Fiser Béla; Bela Fiser; Фішер Бейло; Sikora Emőke; Kristály Ferenc; Viskolcz Béla (Elsevier, 2020)
Abstract. By applying ultrasonic cavitation, palladium particles were deposited onto the surface of two different types of carbon nanotubes (nitrogen-doped bamboo-shaped carbon nanotubes, N-BCNT and multiwalled carbon nanotubes, MWCNT). To achieve this, palladium ions have been reduced by the adsorbent (N-BCNT or MWCNT) itself. Hydroxyl functional groups were identified on the surface of the MWCNTs, while amine groups have been found on the N-BCNTs. The Zeta potential was lower (−9.8 mv) in the case of the N-BCNT sample, than for MWCNT (−6.1 mV), which was in accordance with their different dispersibility in aqueous phase. The incorporated nitrogen atoms and their oxidized forms within the N-BCNT structure lead to increased adsorption capacity and thus, this type of nanotube is more efficient adsorbent for Pd particles, than MWCNT. The higher adsorption capacity of the N-BCNTs can be explained by the presence of nitrogen atoms which increase the interaction between the Pd and nanotubes. Both Pd/nanotube systems show high catalytic activity (after 30 min – 99% aniline yield) in hydrogenation of nitrobenzene to aniline. Thus, palladium coated carbon nanotubes were synthetized in a one-step reduction procedure, and the produced composites are applicable as catalysts in heterogeneous hydrogenation reactions.
Editorial board: https://www.sciencedirect.com/journal/journal-of-materials-research-and-technology/about/editorial-board
Contents: https://www.sciencedirect.com/journal/journal-of-materials-research-and-technology/vol/9/issue/3
Keywords: Palladium; Adsorption; Nitrogen doped; Carbon nanotubes